FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN BEROBAT PADA PASIEN TUBERCULOSIS BERDASARKAN THEORY OF PLANNED BEHAVIOR - laksono, eko budi; Erawati, Meira; Johan, Andrew (Jurnal Borneo Cendekia, 2024)
Compliance with treatment is a term that refers to the extent to which a patient follows instructions and carries out treatment recommended by medical personnel. Compliance includes attitudes, subjective norms and perceived behavioral control as well as intentions that can increase compliance based on the theory of planned behavior. The aim of the research is to analyze the factors that influence treatment compliance behavior in tuberculosis patients based on the theory of planned behavior. This type of research is quantitative research with a cross sectional approach. The population in this study were TB patients in general polyclinics spread across the Genuk District and Pedurungan District Work Areas. The sampling technique was purposive sampling with a total of 108. The results of the study found that statistical tests of the variables attitude, subjective norms, perceived behavior control and intention found a significant relationship with adherence to taking medication in tuberculosis patients. Multivariate test results show that the subjective norm variable is the main predictor of medication adherence in tuberculosis patients. Pulmonary Tuberculosis sufferers can recover if the sufferer takes medication regularly so it is recommended that sufferers adhere to taking medication regularly and obey the supervisor by listening to advice for recovery. Keywords: Medication Adherence; Attitude; Subjective norms; Perceived behavior control; Intentions